Narcissism at Work Personality Disorders of Corporate Leaders - Germain, Marie-Line (Springer International Publishing, 2018)
This book explores the damaging effects of personality disorders in corporate leaders, particularly in regard to organizational variables including employee productivity, motivation, well-being, retention, and ultimately, the organization's bottom line. While helping employees recognize and understand the overt and covert characteristics of malignant narcissism, Narcissism at Work offers solutions and coping strategies vital for employees, industrial psychologists, human resource professionals, and organizational leaders in order to optimize business functions and increase employee well-being.